GAMBARAN PERAN AYAH DALAM PENGASUHAN ANAK USIA 5-6 TAHUNDI TAMAN KANAK-KANAK AISYIYAH BUSTANUL ATHFAL V KECAMATAN BUKIT RAYA KOTA PEKANBARU - ', Marhamah; Novianti, Ria; ', Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on observations in Aisyiyah Bustanul Athfal V kindergarten Bukit Raya Pekanbaru, most fathers of children always busy to work, so it gives less time for their children. This study was purposed to determine descriptipn of fathering in parenting at ages 5-6 years in kindergarten of Aisyiyah Bustanul Athfal V at Bukit Raya Pekanbaru. This study has used descriptive method. The population of this research was80 fathers of children aged 5-6 years in kindergarten Aisyiyah Bustanul Athfal V Bukit Raya Pekanbaru. The sampling in this study using the formulaof Taro Yamane. Based on a formula that has been used, the sample is 44 fathers. The data collection techniques was a questionnaire. The results showed that the description of fathering inparentingat ages 5-6 years in kindergarten Aisyiyah Bustanul Athfal V Bukit Raya Pekanbaru review from Paternal Accessibility indicator shows the percentage of 75.14% with criteria of